ESTIMASI VALUE AT RISK DAN EXPECTED TAIL LOSS DENGAN GENERALIZED ASYMMETRIC STUDENT-T DISTRIBUTION UNTUK RETURN ASET TUNGGAL - , ARIF AULIA RAHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis explain about risk use Value at Risk and Expected Tail Loss estimation with Generalized Asymmetric Student-t Distribution for single asset return. Generalized Asymmetric Student-t Distribution is generalization of student-t distribution and skew student-t distribution. This distribution have characteristic heavy tailed and asymmetric. So,Value at Risk and Expected Tail Loss with Generalized Asymmetric Student-t Distribution give a good risk estimation.